Strengthening interpretive and representational skills in quadratic function through Genially - Moreno Páez, Jimmy Alejandro (Rastros Rostros, 2022)
The implementation of the research sought to establish how the application of a digital tool, called Genially, contributes to the development of interpretive and representative skills of the quadratic function, implementing a didactic strategy, to the students of the tenth grade of the educational institution Juan Pablo II. de Villavicencio, by obtaining low results in tests presented, such as SABER 11th and PISA FOR SCHOOL, shortcomings in variational thinking, in algebraic procedures that need to model situations, to generate analysis and representation, as well as little interest in the subject of mathematics, by having teachers who put aside technological tools and digital spaces, for the master classTherefore, the research is based on the theories of variational thinking, mathematical modeling, quadratic function, "Genially" digital tools and resources, and competency-based education, working through fundamental phases, developed in stages, according to thecharacteristics of each mixed research, based on the implementation of quantitative and qualitative instruments, such as the diagnostic test, semi-structured interviews and an exit test.Finally, from the systematization and analysis of the information collected, it was found that the students improved their performance in the interpretation and representation skills, from variational thinking and problem situation modeling, when using Genially, in addition, they appropriated the theme of quadratic function, without limiting knowledge to the classroom, the math class was in accordance with their interests, evidencing the need for teachers to evolve in accordance with technological advances.
Keywords: Genially; interpretation; representation; variational thinking; modeling and quadratic function